Formula Isolat Protein Kedelai dan Serat Pangan untuk Anak dengan Alergi Protein Susu Sapi: Laporan Kasus: Isolate Soy Protein with Dietary Fiber Formula in Children with Cow’s Milk Protein Allergy: Case Report - Fauziah, Mira; Dilantika, Charisma; Sundjaya, Tonny; Pratiwi, Dessy; Kinesya, Edwin; Ekasiwi, Firstya Diyah (Universitas Airlangga, 2025)
Background: Cow's milk protein allergy (CMPA) represents the most frequently encountered food allergy in pediatric populations younger than three years. Clinical presentations vary widely, including gastrointestinal (GI), respiratory, and cutaneous manifestations. Objectives: The purpose of this case report is to determine the effectiveness of an isolated soy protein formula, enriched with dietary fibre, as a dietary alternative for a child afflicted with cow's milk protein allergy (CMPA). Methods: This study presents a case report concerning a 2-week-old infant who presented with gastrointestinal (GI) symptoms, specifically watery loose stools and vomiting. Given the family and socioeconomic circumstances, neither breast milk nor an amino acid or extensively hydrolyzed formula could be provided. Consequently, the infant received an isolated soy protein formula fortified with dietary fiber. This report further includes a review of the current literature on the utilization of dietary fiber in pediatric populations. Results: The use of isolate soy protein with dietary fibre formula may offer a well-tolerated and nutritionally adequate alternative for children with CMPA, providing paediatricians, nutritionists, and the broader healthcare community with an additional dietary option. Conclusions: The use of soy isolate protein formula with additional fibre suggests a beneficial effect to improve gut microbiota diversity and may improve stool consistency for both constipation and diarrhoea. However, further large-scale studies are needed to confirm its long-term effect, efficacy, and impact on growth and gut health.